2019
DOI: 10.1097/aci.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ocular surface microbiome in allergic disease

Abstract: Purpose of review The purpose of this review is to provide an update regarding new and emerging data on the role of the ocular surface microbiome in allergic disease. Recent findings Recent findings support the role of the microbiome in the pathophysiology of allergic disease of the ocular surface. Summary Understanding the role of the ocular surface microbiome in allergic disease may provide a new target fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…The large fall out of articles was partly due to a high yield of research on the flower iris (publications n = 549) and publications on veterinarian topics (publications n = 859). Based on the inclusion criteria, 76 articles were included: 35 reported on original research (27 on human ocular surface amplicon sequencing, 5 on murine ocular surface amplicon sequencing (Terzulli et al 2015; de Paiva et al 2016; Kugadas et al 2016; St. Leger et al 2017; Wan et al 2018), 1 on intra‐ocular amplicon sequencing and 2 publications using shotgun sequencing), 14 reviews (Willcox 2013; Zegans & Van Gelder 2014; Kugadas & Gadjeva 2016; Lu & Liu 2016; Boost et al 2017; St. Leger & Caspi 2018; Wen et al 2018; Baim et al 2019; Borroni et al 2019; Gallon et al 2019; Watane et al 2019; Cavuoto et al, 2019a, 2019b, 2019c; Ozkan & Willcox 2019) and 27 abstracts (summarized in Table ). When taking into account only amplicon sequencing research on human ocular surface, there is an evident increase in original publications since 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The large fall out of articles was partly due to a high yield of research on the flower iris (publications n = 549) and publications on veterinarian topics (publications n = 859). Based on the inclusion criteria, 76 articles were included: 35 reported on original research (27 on human ocular surface amplicon sequencing, 5 on murine ocular surface amplicon sequencing (Terzulli et al 2015; de Paiva et al 2016; Kugadas et al 2016; St. Leger et al 2017; Wan et al 2018), 1 on intra‐ocular amplicon sequencing and 2 publications using shotgun sequencing), 14 reviews (Willcox 2013; Zegans & Van Gelder 2014; Kugadas & Gadjeva 2016; Lu & Liu 2016; Boost et al 2017; St. Leger & Caspi 2018; Wen et al 2018; Baim et al 2019; Borroni et al 2019; Gallon et al 2019; Watane et al 2019; Cavuoto et al, 2019a, 2019b, 2019c; Ozkan & Willcox 2019) and 27 abstracts (summarized in Table ). When taking into account only amplicon sequencing research on human ocular surface, there is an evident increase in original publications since 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 24 However, diseases may change the microbiota composition of the OS, negatively affecting the protective role of the microbiota and causing it to be harmful. 21 , 25 27 …”
mentioning
confidence: 99%
“…Numerous studies have shown a close relationship of dysbiosis and development of allergic disease in different anatomical areas (12). In particular, several studies have related skin diseases, such as psoriasis and atopic dermatitis, to abundances of certain fungal and bacterial species, including Kocurias and Malassezia (34)(35)(36).…”
Section: The Microbiota's Contribution To Allergic Conjunctivitismentioning
confidence: 99%
“…Finally, the other main player emerging in recent years is the resident microbiota and its contribution to inflammatory response ( 10 ). Some authors report the existence of a kind of symbiosis between commensal microbiota, lymphocytes and epithelial cells ( 11 ) and suggest that the allergic response may be influenced by an ocular surface dysbiosis (microbial imbalance) affecting their physiology and integrity ( 12 ).…”
Section: Introductionmentioning
confidence: 99%